PROBLEMS AND PROSPECTS OF MERGER AND ACQUISITION DECISION IN BANKING SECTOR IN NEPAL - Bhimire, Punam (Prajnik Bimarsha प्राज्ञिक विमर्श, 2023)
The main purpose of this study is to find out the factors that would lead to making decision regarding going for merger and acquisition among the banks in Nepalese banking sector. This paper finds out various factors that would affect merger and acquisition decision in banking sector based upon previous studies, and tries to check whether these are significant in case of Nepalese banking sector or not. Based upon the previous studies done by various scholars, nine factors along with their corresponding hypothesis have been used for study. The nine factors are: emphasis on increasing income, emphasis on increasing sales of services, emphasis on financial diversification, emphasis on cost efficiency, emphasis on obtaining stronger position in market, emphasis on better branding, emphasis on achieving security, emphasis on fulfilling regulations requirement from regulatory authorities and emphasis on fulfilling capital requirement.